First Report of Brachycaudus schwartzi (Bórner) from Peru (Hemiptera: Aphididae) - Díaz, Walter (2007)
The species Brachycaudus schwartzi (Bórner), “brown peach aphid”, is reported for the fifi rst time from Peru. This species has been collected in Tacna Department. Voucher specimens were deposited in the Colección Referencial de Insectos of the Centro de Diagnóstico de Sanidad Vegetal, SENASA, Lima, Peru